Spent mushroom substrate of Pleurotus pulmonarius: a source of easily hydrolyzable lignocellulose - Corrêa, Rúbia Carvalho Gomes; da Silva, Bruna Polacchini; Castoldi, Rafael; Kato, Camila Gabriel; de Sá-Nakanishi, Anacharis Babeto; Peralta, Rosely Aparecida; de Souza, Cristina G M; Bracht, Adelar; Peralta, Rosane Marina (Folia microbiologica, 2016)
Pleurotus pulmonarius was cultivated on a corncob-based substrate for producing of mushrooms and for assessing the transformation of the lignocellulosics during the development of fungal biomass. Associated events, such as the release of relevant enzymes and the H2O2 generation, were also monitored. The peaks of laccase and catalase activities occurred at the 5th day and that of Mn peroxidase at the 30th day, simultaneously with a high activity of superoxide dismutase. Increase in the endocellulase and xylanase activities was observed after 10 days, with maximal activities achieved during the 20-30-day period. Maximal values of H2O2 were found after 10 days of cultivation. Electron microscopy and Fourier transform infrared (FTIR) spectroscopy showed strong alterations in the lignocellulosic fibers. The uncultivated and the cultivated substrates at different times were hydrolyzed with commercial cellulase and β-glucosidase. The highest values of reducing sugars (110.5 ± 5.6 μmol/mL), being 65 % glucose, were obtained using the 20-day cultivated substrate. After the fruiting stage (first flush), enzymatic hydrolysis of the spent mushroom substrate (SMS) yielded 53.0 ± 2.8 and 77.5 ± 4.0 μmol/mL of glucose and total reducing sugars, respectively. Although the release of reducing sugars of the P. pulmonarius SMS was lower than that obtained after 20 days of cultivation, it was still 50 % higher than that obtained using the uncultured substrate. This observation, combined with the fact that SMS constitutes a residue generated as a by-product of the depletion of an agro-industrial residue, allows to conclude that this material offers an interesting economic perspective for the obtainment of cellulosic ethanol.
Keywords: enzymy; Hydrogen Peroxide; Zea mays; Microscopy, Electron; Pleurotus; spektroskopie infračervená s Fourierovou transformací; Spectroscopy, Fourier Transform Infrared; kukuřice setá; elektronová mikroskopie; lignin; peroxid vodíku; Lignin; Enzymes